Science Literacy Profile of Junior High School Students Based on Knowledge, Competence, Cognitive, and Context Aspects - Yohana Saraswati; Sifak Indana; Elok Sudibyo (IJORER : International Journal of Recent Educational Research, 2021)
Humans are faced with industrial advances based on science and technology to meet the needs of human life and solve problems from related issues based on scientific literacy skills. This study aims to describe students' scientific literacy skills which include aspects of knowledge, aspects of competence, aspects of cognitive, and aspects of the context of junior high school students aged 15 years. This research is a quantitative descriptive analysis research. The instrument used to determine scientific literacy skills was a scientific literacy test consisting of 20 multiple choice questions. The science literacy test was validated by two expert lecturers at the State University of Surabaya and one science teacher at State Junior High School of 32 Surabaya. The research also aims to describe the correlation of scientific attitudes to scientific literacy skills. The instrument used was a response questionnaire with 20 yes and no questions. The results showed that the value of the knowledge aspect was 60.57%, the competency aspect was 60.60%, the cognitive aspect was 59.9%, and the context aspect was 60.19%. Scientific literacy skills can be improved by refraction,strategies, and appropriate learning methods. Teachers need to provide access to learning resources from various literary sources, including browsing information via the internet. Students need to be trained to be literate, hone critical and creative thinking, be competent in making decisions to solve problems, and communicate systematically.